2021
DOI: 10.3389/fgene.2021.633295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA in Sheep Intramuscular Fat and the Role of miR-193a-5p in Proliferation and Differentiation of 3T3-L1

Abstract: Intramuscular fat (IMF) is one of the most critical parameters affecting meat quality and mainly affected by genetic factors. MicroRNA as an important regulatory factor, which is still a lack of research in the development of sheep IMF deposition. We used RNA sequencing (RNA-seq) and cell-level validation to explore the role of miRNA in IMF deposition. As for this purpose, longissimus thoracis et lumborum (LTL) samples of 2 month-old (Mth-2) and 12 months-old (Mth-12) Aohan fine-wool sheep (AFWS) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…In this interaction network, some genes related to myofiber type pathways associated with the troponin complex (such as TNNI2 , TNNC2 and TNNT3 ), actin binding ( ACTN3 ) and glycolysis/gluconeogenesis (such as GRK6 , PKM , EPHA , ALDOA and PGM1 ), which are negatively regulated by eca-miR-193a-5p or/and eca-miR-1379, showed higher expression in BF (higher fast muscle fiber population). According to previous reports, miRNA-193a-5p mostly functions in the context of cell proliferation and differentiation, including tumor or cancer development and 3T3-L1 preadipocyte proliferation and differentiation [ 44 , 45 , 46 ]. For instance, the overexpression of miR-193a-5p can inhibit 3T3-L1 preadipocyte proliferation and differentiation by targeting ACAA2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this interaction network, some genes related to myofiber type pathways associated with the troponin complex (such as TNNI2 , TNNC2 and TNNT3 ), actin binding ( ACTN3 ) and glycolysis/gluconeogenesis (such as GRK6 , PKM , EPHA , ALDOA and PGM1 ), which are negatively regulated by eca-miR-193a-5p or/and eca-miR-1379, showed higher expression in BF (higher fast muscle fiber population). According to previous reports, miRNA-193a-5p mostly functions in the context of cell proliferation and differentiation, including tumor or cancer development and 3T3-L1 preadipocyte proliferation and differentiation [ 44 , 45 , 46 ]. For instance, the overexpression of miR-193a-5p can inhibit 3T3-L1 preadipocyte proliferation and differentiation by targeting ACAA2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, miRNA-193a-5p mostly functions in the context of cell proliferation and differentiation, including tumor or cancer development and 3T3-L1 preadipocyte proliferation and differentiation [ 44 , 45 , 46 ]. For instance, the overexpression of miR-193a-5p can inhibit 3T3-L1 preadipocyte proliferation and differentiation by targeting ACAA2 [ 46 ]. A study by Ju et al showed that miR-193-3p may contribute to the regulation of oxidative myofibers in chickens by targeting the PPARGC1A gene [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, our results indicated that RPL34-AS1 interacted with miR-575 to promote the expression of ACAA2, and inferred a novel mechanistic role of RPL34-AS1/miR-575/ACAA2 axis in regulating the progression of ESCC. The upregulation of miR-193a-5p inhibited 3 T3-L1 preadipocyte differentiation, leading to a decrease in fatty acid related gene ACAA2 [ 44 ]. Furthermore, nonalcoholic steatohepatitis (NASH) related differential lncRNAs were associated with predicted protein-coding targets of ACAA2 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reads aligned to the reference genome were aligned with the miRNA precursor and mature sequences in the miRBase V.22.1 ( 33 ) to obtain known miRNAs. The Rfam ( 34 ) was used to filter ncRNAs and repeats sequences such as ribosomal RNA (rRNA), transfer RNA (tRNA), small nuclear RNA (snRNA) and small nucleolar RNA (snoRNA), and at that time, the types and numbers of these sequences were counted. The sRNAs that cannot be aligned with Rfam and miRBase were aligned to the reference genome, and the surrounding sequences were intercepted using miRDeep2 ( 35 ) software for secondary structure prediction to identify new miRNAs.…”
Section: Methodsmentioning
confidence: 99%